Trends and determinants of India’s virtual water trade in crop products - Kannan, Elumalai; Kumar, Anjani (International Food Policy Research Institute, 2023)
This paper analyzed the determinants of India’s virtual water trade in crops and crop products for the period 2001 to 2020. The study used product data at the 6-digit level of commodity classification, covering 206 commodities traded across 218 partner countries. Analysis shows that India has a favorable virtual water trade balance and terms of trade with its partner countries. Among the commodities traded, rice accounted for over one-fourth of the total volume of virtual water exported, and sunflower/safflower oil constitute over one-third of the total volume of virtual water imported. No consistent pattern was observed with regard to the level of endowment of water resources of export destination countries. Gravity model results revealed, as expected, that partner countries’ GDP and population size had a positive effect on virtual water exports, while distance had a negative effect. The coefficient of membership in a free trade agreement (FTA) was negative and statistically significant, implying that FTA member countries are sensitive to the trading of water-intensive agricultural products. The effect of amount of arable land on virtual water exports was negative; this implies that larger virtual water exports correlate with land constraints in a destination country that impede domestic agricultural production. The water endowment variables did not show any significant relationship with virtual water export flows, which confirms the finding in the literature that the water stress of a partner countries does not affect the direction of virtual water flows.